(untitled) (Research, Society and Development, 2021)
This study is a literary review that aims to identify obstetric and perinatal complications during the period of the COVID-19 pandemic in order to reduce the consequences, where it plays a relevant role in the integral health of the patient providing well-being and avoiding adverse effects. Data collection took place between August and September from the Latin American and Caribbean Literature and Health Sciences, Databases in Nursing and Medical Literature Analysis and Retrieval System Online database. The following descriptors were used for the search strategy: pre-established by the Health Sciences Descriptors (DECS): "Labor Complications", "COVID-19", "Puerperal Infection" and "Infectious Complications in Pregnancy". After the eligibility process of the studies, we identified, analyzed and used 9 articles published between 2019 and 2021, referring to complications in pregnancy and in the postpartum or puerperal period. Thus, the information collected in the study analysis comprises several updated discussions on the theme, also elaborated in the pandemic scenario by COVID-19, which fostered the research of integrative review. It is concluded that it is important to emphasize that due to the changes resulting from the pandemic, professional preparation should be special and women should be offered adequate and qualified support, that being said, it is necessary that professionals know the symptoms of COVID-19 to assist in the proper and proper management of the care of the pregnant woman and the baby. However, it is worth mentioning the importance of studies on the subject, due to the scarcity of concrete studies, requiring more extensive research and with a need to know even more about the risks that can be caused during pregnancy-puerperal and perinatal.